REGULATION OF REVENUES OF LOCAL BUDGETS (World Economics and Finance Bulletin, 2023)
This article examines the reforms in the field of tax policy of the Republic of Uzbekistan, changes in the local tax system and the views of economists on the tax system of the country. It also analyzes the country’s revenues by type of tax, state budget revenues by type of tax, indicators for the last three years, as well as the achievements and shortcomings of the local tax system. Scientific conclusions and recommendations on further development of the tax system in Uzbekistan and, as a result, support for production, improvement of the mechanism of local tax incentives have been formed.
Keywords: local budget; tax system; tax policy; local taxes